Impaired P2Y12 inhibition by clopidogrel in kidney transplant recipients: results from a cohort study. Issue 1 (December 2016) - Muller, Clotilde; Messas, Nathan; Perrin, Peggy; Olagne, Jerome; Gautier-Vargas, Gabriela; Cognard, Noelle; Caillard, Sophie; Moulin, Bruno; Morel, Olivier
Abstract Background Cardiovascular complications represent a major cause of morbidity and mortality for patients who received kidney transplantation (KT). However, the impact of KT and chronic immunosuppression on platelet response to clopidogrel in patients undergoing coronary or peripheral revascularization procedures remains unclear. This cohort study compares platelet responsiveness to clopidogrel as assessed byvasodilator-stimulated phosphoprotein (VASP) phosphorylation. Methods The study population was divided between chronic kidney disease (CKD) patients who underwent KT (n = 36) and non-transplanted CKD patients (control group, n = 126). Patients were on maintenance antiplatelet therapy with clopidogrel 75 mg daily for at least 8 days. The mean platelet reactivity index (PRI) VASP values and the prevalence of high on-treatment platelet reactivity (HPR, defined as PRI VASP ≥61 %) were compared. Results The mean PRI VASP value was significantly higher in the transplant group (60.1 ± 3 vs 51.2 ± 1.6 %;p =0.014). HPR was significantly more common in the transplant group on clopidogrel maintenance therapy (58 vs. 31 %; p = 0.011). KT was the only independent predictor of HPR (odds ratio: 2.6; 95 % confidence interval: 1.03–6.27, p = 0.03). The effect of treatment with calcineurin inhibitors on clopidogrel response could not be analyzed separately from the kidney transplant status. Conclusions KT is associated with an increased prevalence of HPR. Our results suggest that plateletfunction tests may be clinically useful for the management of this specific population.